Developing Ethic Game (Ethnomathematics Game): The Instructional Media of Culture Mathematics with Tringo by Ki Hadjar Dewantara - Sayyidati Fatimah Az-Zahroh; Zahid Zufar At Thaariq; Ence Surahman; Chania M. Widyasari; Muhammad Syifa’ul Qolbi; Risma Chulashotud Diana (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2019)
One of the most important steps in having educational process with the media. The media itself represents the component of Language Leaning. In researchers’ context, which is Math, the subject matter represents the content itself. Most of the times, our students face difficulty in learning the content—Math subject. Therefore, the objective of this study is to produce an instructional media that might ease the students in learning Mathematics easier and meaningful. Our interest is developing an instructional media that help students to also learn culture as its additional material. We develop ETHIC GAME (Ethnomathematics Game) as an integrated and augmented reality-based (AR) instructional media that combine mathematics and culture. Based on Edgar Dale’s theory on learning, the students can undergo the meaningful learning experience when they learn, observe, and listen to the media by themselves. We decide then to make an instructional media that also use such kind of principle that is TRINGO (Ngerti, Ngrasa, Nglakoni – or Understanding, Experiencing, Doing) by Ki Hadjar Dewantara. The development method used in this study refers to Lee Owen model of development. In the end, by having ETHIC GAME as instructional media, students learn more insightful and meaningful Mathmatics and culture—not only to make the learning process more authentic, but also to make the learners preserve the national culture. Indicates how easy the users in using the application which shows 100% of the users stated that there is no difficulty in using it. So, this instructional media can be used easily and fun